A socio-structural analysis of crime in the city of Tshwane, South Africa - Gregory Breetzke (South African Journal of Science)
High and rising levels of crime plague post-apartheid South Africa. A common explanation for these high crime rates relates the country's unique socio-political past to a system of ineffective social control mechanisms that suggest high levels of social disorganisation within certain communities. Other explanations emphasise the presence of disaffected youths and deprivation, as well as the rapid immigration of people from neighbouring African countries into South Africa. I examined a number of these socio-structural explanations of crime on contact crime rates in the city of Tshwane, South Africa. The findings are largely consistent with the social disorganisation theory, as well as with what has previously been suggested in local literature. In order to supplement these preliminary findings, the effects of the same socio-structural explanations on contact crime rates were determined for predominantly Black, White, and 'Mixed' (containing a mix of both Black and White residents) suburbs using spatial regression models. Evidence from these analyses suggests that the effects of the various socio-structural explanations do not appear to traverse racial lines. Rather, the findings suggest non-uniformity in terms of the extent to which the various socio-structural factors impact contact crime rates based on race.